“Smart” anticorrosion pigment based on layered double hydroxide: construction and characterization - Kovalenko, Vadym; Kotok, Valerii (Eastern-European Journal of Enterprise Technologies, 2019)
Paint coatings are widely used for decorative purposes and to prevent corrosion of metal surfaces. However, regular paint coating only provides passive protection of the metal. To create an active type of corrosion protection, various anti-corrosion additives are added to paint formulations. As a result of analyzing available data, a bi-functional (colored and anti-corrosion) pigment was theoretically constructed as monophase Zn-Al-tripolyphosphate LDH with the generalized formula Zn0.8Al0.2(P3O10)0.04. In this LDH, Zn2+ as “host” cation and Al3+ as “guest” cation govern white color of the pigment, and intercalated tripolyphosphate-anions – corrosion inhibitor. A continuous constant pH synthesis at a temperature of 70°С was selected as a preparation method. This method was used to prepare theoretically constructed pigment. The crystal structure of the pigment sample was studied by means of X-ray diffraction, morphology and particle size were determined by means of scanning electron microscopy, thermal properties were evaluated by means of thermogravimetry. Color characteristics were recorded using the color comparator, anti-corrosion properties were evaluated by recording anodic polarization curves of 08KP steel in 5 % (wt.) Na2SO4 solution with and without the pigment extract. By means of X-ray diffraction analysis, it was found that bi-phase precipitate, containing the constructed LDH (with Zn(OH)2 structure) and Zn-Al LDO (ZnO structure) was formed. This indicated partial decomposition of LDH during synthesis, but the reason for it is unknown. By means of SEM, the formation of agglomerates of the same particles with high surface area was found. The study of color characteristics revealed that the prepared pigment has high whiteness value (diffuse reflection coefficient above 90 %, color purity below 1 %, lightness above 96 %). This is due to the color of both LDH and LDO phases. By recording anodic polarization curves, it was found that corrosion rate in the presence of water extract of the pigment is lower by 5.36 times (corrosion current density decreased from 5.63 mA/cm2 to 1.03 mA/cm2. All of this shows that a bi-functional pigment was prepared, which has great pigment properties, high whiteness, and high anti-corrosion properties.